Biocompatibility of bismuth silicate coatings deposited on 316L stainless steel by sol-gel process (2017)
Bismuth silicate, (BSO) thin films have been fabricated by sol–gel process. The stable sol was synthesized by using bismuth nitrate (III) pentahydrate and tetraethyl orthosilicate (TEOS). The films were deposited by spin-coating at 1500 rpm on Stainless Steel 316L. The films were characterized by Atomic Force Microscopy (AFM), Scanning Electron Microscopy (SEM), X-ray diffraction (XRD) besides the measured of the films thickness. This study aimed to evaluate the cell adhesion and cellular proliferation of osteoblast cells on BSO thin films and substrate 316L by MTT assay. It is concluded that the growth of osteoblasts is homogeneous in the surface of the coatings indicating that the medium offered by the films does not present active cytotoxicity and exceed in large number the level of cellular growth compared to Stainless Steel